(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
The notion of case has been a controversial one, yet the grammatical terminology has survived right from traditional Grammar to the current grammatical theories. This paper critically examines the notion of case within different grammatical frameworks. Our interest is mainly on the role of syntax and semantics in case determination and the level of grammatical analysis (deep or surface) at which case is assigned. The paper looks at the notion of case as conceived in traditional grammar and the explores how the concept has been adapted to antecedent grammatical theories up to the Principles and parameters theory. The paper concludes that in all the grammatical models, Case has both syntactic and semantic relevance.